NIR-II light evokes DNA cross-linking for chemotherapy and immunogenic cell death. (1st April 2023) - Huang, Yun; Wei, Dengshuai; Wang, Bin; Tang, Dongsheng; Cheng, Ailan; Xiao, Shengjun; Yu, Yingjie; Huang, Weiguo
Abstract: As a DNA damaging agent, oxaliplatin (OXA) can induce immunogenic cell death (ICD) in tumors to activate the immune system. However, the DNA damage induced by OXA is limited and the ICD effect is not strong enough to enhance anti-tumor efficacy. Here, we propose a strategy to maximize the ICD effect of OXA through the mild hyperthermia generated by nanoparticles with a platinum (IV) prodrug of OXA (Pt(IV)-C16) and a near-infrared-II (NIR-II) photothermal agent IR1061 upon the irradiation of NIR-II light. The mild hyperthermia (43 °C) holds advantages in two aspects: 1) increase the Pt-DNA cross-linking, leading to enhanced DNA damage and apoptosis; 2) induce stronger ICD effects for cancer immunotherapy. We demonstrated that, compared with OXA and photothermal therapy of IR1061 alone, these nanoparticles under NIR-II light irradiation can significantly improve the anti-cancer efficacy against triple-negative breast cancer 4T1 tumor. This new strategy provides an effective way to improve the therapeutic outcome of OXA. Statement of significance: OXA could induce immunogenic cell death (ICD) via stimulating immune responses by increasing tumor cell stress and death, which triggers tumor-specific immune responses to achieve immunotherapy. However, due to the insufficient Pt-DNA crosslinks, the ICD effect triggered by OXA cannot induce robust immune response. Mild hyperthermia has great potential to maximize the therapeutic outcome of oxaliplatin by increasing the Pt-DNA cross-linking to augment the immunoresponse for enhanced cancer immunotherapy. Graphical abstract: Image, graphical abstract